Kebangkitan Kristus dan Upaya Membangkitkan Manusia dari Kematian: Telaah Teologis Terhadap Transhumanisme-krionik - Yahya Wijaya; Defrita Rufikasari (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2023)
AbstractThe resurrection of Christ is often associated exclusively with the context of Easter, the redemption of the sinful humans, and the hope of the future resurrection of the faithful. The resurrection from the dead is mentioned several times both in the Old and the New Testaments. Interestingly, both Christianity and transhumanism tend to deny death. In terms of Christianity, that is indicated in the theological view of the resurrection of Christ and the believers; while in that of transhumanism the denial of death is implied in thedevelopment of nanotechnology and cryogenics aiming at raising people from the dead. They both promise an incorruptible and antifragile life. But do they share the same meeting point or have a common ground? Can the resurrection of Christ be interpreted from the vision of transhumanism that opens up opportunities for humans to improve their quality of life? This writing describes the views of several thinkers about transhumanism and their relations to theology, especially concerning the issue of the resurrection. The method used is qualitative research with a descriptive model based on a literature study and a public  theology approach putting into discussion the existing thoughts on transhumanism, their relationshipswith religions, and the interpretation of Christ’s resurrection as the meeting point of the redemption theology and transhumanism. AbstrakPemaknaan kebangkitan Kristus acapkali hanya dilekatkan dalam konteks Paskah, penebusan dosa manusia dan harapan akan kebangkitan yang sama akan dialami oleh umat beriman. Peristiwa kebangkitan dari kematian sebetulnya beberapa kali muncul dalam Alkitab baik Perjanjian Lama atau Baru. Menariknya, jika dilihat sekilas, baik Kekristenan dan Transhumanisme nampak sama-sama menolak kematian. Kekristenandengan pandangan teologi kebangkitan Kristus dan orang beriman, sedangkan transhumanisme dengan pengembangan nanoteknologi dan kriogenik yang membangkitkan orang dari kematian. Keduanya nampak sama-sama menjanjikan kehidupan yang tidak fana dan rapuh. Namun benarkah keduanya memiliki titik temu yang sama? Memiliki landasan yang sama? Apakah kebangkitan Kristus nantinya akan dapat juga dimaknai dari visi transhumanisme yang membuka peluang bagi manusia meningkatkan kualitas hidupnya? Penulisan ini bertujuan untuk menguraikan pandangan-pandangan beberapa pemikir tentang transhumanisme dan kaitannya dengan teologi, khususnya kebangkitan dari mati. Metode yang digunakan adalah penelitian kualitatif dengan model deskriptif berdasarkan studi pustaka dan pendekatan teologi publik untuk mendialogkan pemikiran-pemikiran yang ada terkait topik transhumanisme, relasi dengan agama, dan pemaknaan kebangkitan Kristus sebagai titik temu dari karya penebusan dan transhumanisme.